Global, regional and national epidemiological trends of multiple myeloma from 1990 to 2021: a systematic analysis of the Global Burden of Disease study 2021 - Linmin Zhuge; Xiaowu Lin; Ziwei Fan; Mengxian Jia; Chaowei Lin; Minyu Zhu; Honglin Teng; Guoliang Chen (Frontiers in Public Health)
BackgroundMultiple myeloma (MM) is a growing global public health challenge. Known epidemiological data suggest that MM accounts for approximately 10% of all hematologic malignancies and remains the second most common hematologic cancer worldwide. This study utilized data from the 2021 Global Burden of Diseases (GBD) study to evaluate the prevalence, incidence, mortality, disability-adjusted life years (DALYs), and attributable risk factors of MM from 1990 to 2021, and to project future trends for the next 15 years.MethodsGBD 2021 data were analyzed to assess MM’s global burden using four key epidemiological measures: prevalence, incidence, mortality, and DALYs. Estimates are reported per 100,000 population with uncertainty intervals (UI). Temporal trends were assessed through estimated annual percentage change (EAPC) and 95% confidence intervals (CI). All analyses were conducted using R version 4.2.1.ResultsFrom 1990 to 2021, global MM prevalence, incidence, mortality, and DALYs more than doubled, particularly among males. All Social-Demographic Index (SDI) regions showed increases in ASPR, ASIR, ASMR, and ASDR (all EAPCs >0), with the middle SDI regions exhibiting the most rapid growth. ARIMA model predictions suggest that the MM burden will continue rising over the next 15 years. The proportion of MM cases attributable to high BMI also increased globally, from 6.40% in 1990 to 7.96% in 2021. MM primarily affects older adults, with the highest incidence observed in the 70–74 age group and the highest mortality rate recorded in the same age range.ConclusionMM presents an escalating global health challenge. Targeted preventive interventions and improvements in diagnosis, treatment, and care are critical, especially in underdeveloped regions, to address the growing global burden of MM.